Antecedents of Consumer Adoption of Over-the-Top Services in South Korea. Issue 3 (3rd July 2022) - Jeong, Dahye; Lee, Minyoung; Park, Eunil
ABSTRACT: This study aims to explore South Korean consumers' adoption of over-the-top (OTT) services, which are one of the most innovative media services available today. We employed two user-oriented approaches – the diffusion of innovation theory and the technology acceptance model – to propose an integrated consumer acceptance model for OTT services. We analyzed online survey data from 1, 302 South Korean users of OTT services. Both structural equation modeling and confirmatory factor analysis methods indicated that OTT's perceived compatibility, observability, and trialability based on the diffusion of innovation theory, and its perceived usefulness based on the technology acceptance model, are key determinants of consumer attitude toward OTT services, which are significantly correlated with their intention to use these services. Based on this study's findings, several implications and research directions were presented, considering both the applicability and significance of the proposed research model.